A social network analysis of the Philippine seaweed farming industry: Unravelling the web. (August 2020) - Suyo, Jee Grace B.; Le Masson, Virginie; Shaxson, Louise; Luhan, Maria Rovilla J.; Hurtado, Anicia Q.
Abstract: Seaweed farming is a major economic endeavor among the households in the key seaweed-production areas in the Philippines because of its high profitability potential relative to farming effort. This study used Social Network Analysis (SNA) to explore the social structure and the nature of support mechanism at the production segment of the seaweed value chain to understand the differential access of women and men to information, resources, and services. The data was obtained from Focus Group Discussions (FGD) with 115 seaweed farmers in Zamboanga City, Bohol, and Tawi-Tawi. The resulting social support maps show a strong reliance on internal support sources (e.g. family) across the selected parameters (training, farm preparations, product flow) and a gender difference on the extent of access to external sources. This study highlighted the relevance of using SNA in value chain analysis (VCA) to understand the relationship patterns among the actors and their implications on policy making and overall governance of the seaweed industry.